A Post‐2013 Dropoff in Total Ozone at a Third of Global Ozonesonde Stations: Electrochemical Concentration Cell Instrument Artifacts?. Issue 11 (4th June 2020) - Stauffer, Ryan M.; Thompson, Anne M.; Kollonige, Debra E.; Witte, Jacquelyn C.; Tarasick, David W.; Davies, Jonathan; Vömel, Holger; Morris, Gary A.; Van Malderen, Roeland; Johnson, Bryan J.; Querel, Richard R.; Selkirk, Henry B.; et al.
Abstract: An international effort to improve ozonesonde data quality and to reevaluate historical records has made significant improvements in the accuracy of global network data. However, between 2014 and 2016, ozonesonde total column ozone (TCO; O3 ) at 14 of 37 regularly reporting stations exhibited a sudden dropoff relative to satellite measurements. The ozonesonde TCO drop is 3–7% compared to satellite and ground‐based TCO, and 5–10% or more compared to satellite stratospheric O3 profiles, compromising the use of recent data for trends, although they remain reliable for other uses. Hardware changes in the ozonesonde instrument are likely a major factor in the O3 dropoff, but no single property of the ozonesonde explains the findings. The bias remains in recent data. Research to understand the dropoff is in progress; this letter is intended as a caution to users of the data. Our findings underscore the importance of regular ozonesonde data evaluation. Plain Language Summary: Balloon‐borne ozonesondes provide accurate measurements of atmospheric ozone (O3 ) from the surface to above 30 km with high vertical resolution. Dozens of global stations have regularly launched ozonesondes for decades, and they provide vital information for improving O3 ‐measuring satellite algorithms, tracking recovery of the stratospheric O3 layer, and our understanding of surface to lower stratospheric O3 changes in an evolving climate. We present the discovery of an apparent instrument artifact that has caused total column O3 measurements from about a third of global stations to drop by 3–7% starting in 2014–2016, limiting their suitability for calculating O3 trends. Work is underway to solve the problem, but the exact cause of the drop is still unknown. This letter serves as a caution to the community of ozonesonde data users. Key Points: We report a drop in ozonesonde total column O3 of 3–7% relative to independent measurements at a third of sites beginning around 2014 Comparisons with satellite stratospheric O3 profiles show the artifact loss peaking at 5–10% or more in the middle and upper stratosphere Changes in the ozonesonde instrument are apparently associated with the dropoff, but no single factor appears to be the cause